2021
DOI: 10.21608/jpp.2021.177770
|View full text |Cite
|
Sign up to set email alerts
|

Potato Growth and Yield as Affected by Foliar Application with Naa Auxin and 6-Ba Cytokinin

Abstract: Two open field experiments were conducted during summer seasons of 2019 and 2020, in a private farm at Abou El-Matamer district, Behiera Governorate, Egypt. Certified imported potato seeds of 'Cara' cv. were used after splitting-up. Cut seedy explants (ca. 40 g) contain two eyes each were planted at 0.80 m wide and 0.20 m apart between hills, using four concentrations of synthetic NAA auxin (control, 25, 50, and 100 mg l -1 ) and four concentrations of the synthetic cytokinin BA (control, 25, 50, and 100 mg l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Walia et al, 2021 obtained consistent results in the potato variety Kufri Girdhari. Kazemiani et al (2012) discovered that 2 mg/l BAP into culture media increased the number of lateral shoots.Similar result was also observed with (Ahmed et al, 2021). For root length results was similar with Krish namurthy et al (2001) but in Polia nthes tuberosa L.…”
Section: Shoot Length and Root Length In Net House And In Fieldsupporting
confidence: 90%
See 1 more Smart Citation
“…Walia et al, 2021 obtained consistent results in the potato variety Kufri Girdhari. Kazemiani et al (2012) discovered that 2 mg/l BAP into culture media increased the number of lateral shoots.Similar result was also observed with (Ahmed et al, 2021). For root length results was similar with Krish namurthy et al (2001) but in Polia nthes tuberosa L.…”
Section: Shoot Length and Root Length In Net House And In Fieldsupporting
confidence: 90%
“…The minimum number of stolons and minitubers were recorded in control. This result was similar with Kumar and Wareing (1972) regarding stolons numbers, Ahmadi et al, (2018) and Ahmed et al, (2021) in case of minitubers nimber.…”
Section: Number Of Stolons and Minitubers In Net House And In Fieldsupporting
confidence: 88%
“…Over the years, many studies have shown that auxin-regulated cell expansion plays an important role in plant development, specifically in primary root growth [164,165], lateral root development [166,167], organ development [168,169], tropism [170,171], apical dominance [172,173], etc. Because of their multifunctionality, auxins can be used in strategic plantations as plant growth promoters, and this approach has shown promising results in sugarcane [174], potato [175], and tomato plantations [176]. Auxins also help to obtain higher yields of good quality carrot seeds [177], improve the root morphology and growth of grafted cucumber seedlings [178], and can be used to alleviate abiotic stresses [179][180][181] The most well-known compound used to treat weeds using auxin-based products in plantations is 2,4-dichlorophenoxyacetic acid (2,4-D), which was discovered in the 1940s and has been used extensively for more than 70 years worldwide.…”
Section: Auxinsmentioning
confidence: 99%